2017
DOI: 10.1017/s104161021700254x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of subjective memory complaints in Vietnamese adults

Abstract: Prevalence of SMCs as well as depressive symptoms was high in this Vietnamese population. Although future research using more detailed measures of subjective memory and which include longitudinal data are required, the need for physicians to routinely assess Vietnamese patients for depression, SMCs, and cognitive impairment may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…born before the end of WWII). The SMC has been recognized as an indicator of aging and depression (Meyer et al, 2018;Smith et al, 1996), with an increasing number of studies suggesting that it may also be an early marker of future nonnormative cognitive decline and progression of dementia (Jorm et al, 2001;Reisberg et al, 2010;St John and Montgomery, 2002;Wang et al, 2004). A recent meta-analysis of longitudinal studies reported that the annual conversion rate of SMC to dementia is 2.3%, and people with SMC are 2.07 times more likely to develop dementia compared with those without SMC (Mitchell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…born before the end of WWII). The SMC has been recognized as an indicator of aging and depression (Meyer et al, 2018;Smith et al, 1996), with an increasing number of studies suggesting that it may also be an early marker of future nonnormative cognitive decline and progression of dementia (Jorm et al, 2001;Reisberg et al, 2010;St John and Montgomery, 2002;Wang et al, 2004). A recent meta-analysis of longitudinal studies reported that the annual conversion rate of SMC to dementia is 2.3%, and people with SMC are 2.07 times more likely to develop dementia compared with those without SMC (Mitchell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is plausible the alcohol-related cognitive impairment in men is mediated by other risk factors. For example, personal and social factors including life dissatisfaction, depression, economic, nancial and relational stressors which are associated with alcohol use among Ghanaian men (47,48) are likewise enduring correlates of SCCs (10,15,49,50). Although more research is required for a better understanding of the relationship between alcohol and SCCs in the Ghanaian context, our results a rm the need for public health intervention to target the reduction in alcohol consumption in both males and females (46).…”
Section: Discussionmentioning
confidence: 71%
“…Age, education, marital status, health insurance status, household wealth index, rural-urban residence, and region of residence were selected as control variables for this study. The selection of these variables as covariates was based on ndings from previous studies (10,18,42) and their availability in the datasets.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for the association between depressive symptomatology and SCD discussed in the literature is that people with a depressive symptomatology "may pay more attention to or monitor their state more closely for negative or problematic symptoms" (p. 1040). 64 This sensitivity to negative changes in personal health states might also be typical for people high on the personality trait of emotionality/neuroticism. 65 Quite a number of studies have investigated the relationship between this personality characteristic and subjective cognitive complaint, consistently finding low to moderate positive associations between both.…”
Section: Discussionmentioning
confidence: 99%